2013
DOI: 10.1108/mmms-09-2012-0013
|View full text |Cite
|
Sign up to set email alerts
|

Safety analysis of thermal creep non-homogeneous thick-walled circular cylinder under internal and external pressure using Lebesgue strain measure

Abstract: Purpose -Safety analysis has been done for thermal non-homogeneous thick-walled circular cylinder under internal and external pressure. The paper aims to discuss these issues. Design/methodology/approach -Transition theory based on the concept of generalized principal Lebesgue strain measure has been used which simplifies the constitutive equations by prescribing a priory the order of the measure of deformation and helps to achieve better agreement between the theoretical and experimental results. Findings -Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Here, B(r) and n(r) are given by Equation (6). The constant C is evaluated by using the boundary condition at r = r o and is given as,…”
Section: Radial Coordinate (R) Volume Reinforcement V(r)mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, B(r) and n(r) are given by Equation (6). The constant C is evaluated by using the boundary condition at r = r o and is given as,…”
Section: Radial Coordinate (R) Volume Reinforcement V(r)mentioning
confidence: 99%
“…Nejad et al [ 5 ] derived exact closed-form solutions as well as finite element analysis for stresses and the displacements in pressurized thick spherical shells made of functionally graded materials with exponentially varying properties subjected to internal and external pressure. Sharma et al [ 6 ] conducted safety analysis for thermal non-homogeneous thick-walled circular cylinder under internal and external pressure by using transition theory based on generalized principal Lebesgue strain measure in order to understand how the possibility of material fracture can be minimized. Sahni and Sharma [ 7 ] obtained creep stresses in a transversely isotropic thick-walled rotating circular cylinder using Seth’s transition theory and measured the effect of external pressure and rotation.…”
Section: Introductionmentioning
confidence: 99%
“…In this problem, we have considered only the principal stresses and it has been shown that [5][6][7][8] transition through τ rr − τ θθ results in creep state for the critical point Q → -1. Thus transition function R is defined as…”
Section: Methods Of Approachmentioning
confidence: 99%
“…Sharma et al [7] investigated thermal creep stresses and concluded that thick-walled circular cylinder under external pressure is better for the designing purpose as compared to homogeneous cylinder. Sharma et al [8] investigated thermal creep stresses for functionally graded thick-walled circular cylinder under pressure and concluded that functionally graded cylinder reduces the possibility of fracture of cylinder. With theoretical analysis and designing in the mind, this paper emphasize on the derivation of simple but reasonably accurate mathematical solutions to a wide range of shell problems.…”
Section: Introductionmentioning
confidence: 99%